Elizabeth (Liz) Dyneley Fell, 1940-2020: The distinguished journalist whose interviews covered major changes in the Australian telecommunications industry - Gerrand, Peter (Journal of Telecommunications and the Digital Economy, 2020)
Liz Fell (7 March 1940 to 13 August 2020), a freelance journalist, was elected a Distinguished Fellow of the Telecommunication Society of Australia in 2003 for her notable and enduring contributions to Australian telecommunications. Amongst others, she carried out brilliant interviews over twenty years (1994-2013) for the Telecommunications Journal of Australia. This article celebrates her notable contributions to Australian telecommunications, and includes references to two of her most famous interviews, with Malcolm Turnbull MP in 2011 and with the Hon. James (Jim) Spigelman AC, Chairman of the ABC, in 2013.